Durability and tribological properties of thermally sprayed wc cermet coating under lubricated rolling-sliding contact - Nuruzzaman, D. M.; Nakajima, A.; Mawatari, T.; Ali, Mohammad Yeakub (IIUM Press, 2007)
Durability and tribological properties of thermally sprayed WC-Cr-Ni cermet coating were investigated experimentally under lubricated rolling with sliding contact conditions. By means of the high energy type flame spraying (Hi-HVOF) method, the coating was formed onto the axially and circumferentially ground roller specimens made of a thermally refined carbon steel. In the experiments, the WC cermet coated steel roller was mated with the carburized hardened steel roller without coating in line contact condition. The coated roller was mated with the smooth non-coated roller under a contact pressure of 1.0 or 1.2 GPa. The coated roller was also mated with the rough noncoated roller under a contact pressure of 0.6 or 0.8 GPa. It was found that the coating on the circumferentially ground substrate shows a lower durability compared with that on the axially ground substrate. This difference appears more distinctly for the higher contact pressure for both smooth and rough mating surface. It was also found that there are significant differences in the tribological properties of WC cermet coating depending on the contact pressure. In addition, depending on the mating surface roughness or substrate surface finish, remarkable differences in the tribological properties such as oil film formation, surface roughness, appearance of the coated surface ,depth of flaking etc. were found.